Case Report: A Novel Compound Heterozygous Mutation in IL-10RA in a Chinese Child With Very Early-Onset Inflammatory Bowel Disease - Dong, Fang; Xiao, Fangfei; Ge, Ting; Li, Xiaolu; Xu, Wuhen; Wu, Shengnan; Zhang, Ting; Wang, Yizhong (Frontiers in Pediatrics, 2021)
Very early-onset inflammatory bowel disease (VEO-IBD) is defined as IBD diagnosed in children younger than 6 years of age. VEO-IBD is often associated with a monogenic etiology or primary immune deficiency. Here, we report the case of a 7-month-old Chinese girl diagnosed with VEO-IBD who had a variant in the interleukin-10 receptor A (IL-10-RA) gene. The patient presented with recurrent fevers, abdominal pain, diarrhea, perianal abscesses, and oral ulcers. Whole-exome sequencing (WES) identified a novel compound heterozygote mutation, c.395T>G (p.Leu132Arg)/ex.1del (p.?), in the IL-10RA gene of the patient. The missense mutation c.395T>G (p.Leu132Arg) was inherited from her mother, and ex.1del (p.?) was inherited from her father. Neither mutation has been reported previously. The IL-10RA function of the patient was defective, as demonstrated by a failure of signal transducer and activator of transcription 3 (STAT3) activation in peripheral blood mononuclear cells (PBMCs) stimulated with recombinant IL-10. The patient underwent matched unrelated peripheral blood hematopoietic stem cell transplantation (HSCT), and the clinical manifestations were dramatically improved. In summary, we identified a novel compound heterozygote mutation, c.395T>G (p.Leu132Arg)/ex.1del (p.?), in IL-10RA that caused VEO-IBD in a Chinese child, which further expands the mutational spectrum of IL-10RA.